Il teatro postdrammatico e i suoi ampi dintorni - Petrini, Alfio (Mimesis Journal, 2018)
The post-dramatic by Hans-Thies Lehmann is available in the Italian bookstores thanks to Cue Press Editors (Bologna 2017) that published it along with the translation written by Sonia Antinori and the afterword by Gerardo Guccini. In a brief anthology of observations, at the end of the book you can find the comments by Giorgio Degasperi (A post-epic theatre), Marco De Marinis (Post-dramatic theatre – overcoming of the representation and the staging), Lorenzo Mango (Crisis of signs and drama of vision), Antonio Attisani (An actually neo-Aristotelian and neo-dramatic overview), Cristina Valenti (Crisis of the dramatic personalization and crisis of the individual as agent of the social conflict), Marco Martinelli (The future of theatre will be small groups).The book names cultural movements, historical periods, theatre companies and artists along a vast timeframe. Lehmann is not the inventor of post-dramatic theatre, but of the definition that titles the book that we consider a precious instrument of study and work.